PENATAAN DAN PANDANGAN HUKUM ISLAM MUHAMMAD SHAHRUR (UINSI Samarinda, 2015)
Muhammad Shahrur is a contemporary scholar who offers a reformist approach to Islamic studies. In bringing forth his ideas especially those related to the Islamic issues, he takes into account sociological backgrounds surrounding them. His thoughts, therefore, are phenomenal and even controversial in some areas such as on the issues of polygamy, inheritance limit, veil, marriage, dowry, and ṭalāq. This article analyzes Shahrur’s thoughts related to these problems. It finds that Shahrur’s ideas are based on the careful observation ofIslamic sciences coupled with theories in natural sciences. He thus argues that the nature of scientific truth is tentative and the Qur’ān as a text is open to different meanings and interpretations.